2013
DOI: 10.1021/jp400498x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Deposition and Characterization of MoS2 Nanolayers on Carbon Nanofibers and Nanotubes

Abstract: We report on the deposition of thin nanolayers of MoS2 material on carbon nanofibers (CNFs) and multiwalled carbon nanotubes (CNTs) by in situ thermal decomposition of (NH4)2MoS4 in oleylamine. The synthesized MoS2@CNF and MoS2@CNT nanocomposites were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), electron energy loss spectroscopy (EELS), and Raman spectroscopy. TEM results indicate that CNFs, as well as CNTs, provide an excellent template for the deposition and growth of MoS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…For LEGr@WS 2 , two diffraction peaks centered at around 2θ=32.6° and 57.2° corresponded to the (100) and (110) planes of hexagonal WS 2 , respectively ,. Impressively, LEGr@WS 2 ‐75 did not exhibit a (002) reflection peak at ∼14°; this peak was typically observed in the bulk analogue, indicating that the material contains single‐layer WS 2 . This result was in good agreement with the SAED data where the diffraction ring on the (002) plane was absent.…”
Section: Resultssupporting
confidence: 85%
“…For LEGr@WS 2 , two diffraction peaks centered at around 2θ=32.6° and 57.2° corresponded to the (100) and (110) planes of hexagonal WS 2 , respectively ,. Impressively, LEGr@WS 2 ‐75 did not exhibit a (002) reflection peak at ∼14°; this peak was typically observed in the bulk analogue, indicating that the material contains single‐layer WS 2 . This result was in good agreement with the SAED data where the diffraction ring on the (002) plane was absent.…”
Section: Resultssupporting
confidence: 85%
“…Bi atoms show a strong photoelectric absorbance capacity under X‐ray radiation and can generate numerous short‐range secondary electrons, thus enhancing the X‐ray deposition in tumor tissues and accelerating the DNA breaking. Ammonium tetrathiomolybdate ((NH 4 ) 2 MoS 4 ) has been introduced in the solvo/hydrothermal production of MoS 2 nanosheets and NPs . We have recently presented the production of 2D polyethyl­ene glycol (PEG)‐ylated MoS 2 nanosheets by solvothermal treatment of (NH 4 ) 2 MoS 4 and PEG‐400 aqueous solution for tumor PTT .…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that MoS 2 /NCNFs composites exhibit lower crystalline structure. [50][51][52][53] In fact, hexagonal structures of MoS 2 have three characteristic diffraction peaks, 54, 55 nevertheless, the diffraction peak of (002) plane (2θ = 14.5°) disappears in this work, demonstrating the presence of "graphene-like" layers are less than five layers, 15,41,53,54,56 which is in accordance with the result of HRTEM (Figure 1h), Please do not adjust margins Please do not adjust margins indicating that the incorporation of carbon nanofiber considerably restrains the aggregation of layered MoS 2 during the carbonized process, leading to the MoS 2 ultrathin and lower crystalline structure. 57 Many reports demonstrated that amorphous MoS 2 expose more active edges and exhibit higher HER activity than crystalline MoS 2 .…”
Section: Electrochemical Measurementsmentioning
confidence: 99%